A IMPRENSA NA CONSTRUÇÃO DA IMAGEM PÚBLICA DO CANDIDATO AFFONSO PENNA NA ELEIÇÃO DE 1906 - Ramos, Thailissa Leticia Andara (2009)
The present work has for objective to analyze the period of electoral propaganda to the presidency of the Republic of 1906, centering its object in the only candidate for president, the miner, Affonso Penna. In this direction it is looked to work, specifically, the paper of the press in the candidacy and the construction of the public image, in the course between August of 1905 the February of 1906, in two Carioca periodicals: O Correio da Manhã and the periodical O Paíz. Between them, the mention of Penna can be analyzed only in the Cartas Mineiras of the Correio da Manhã, which presents the percentage of 37% of contents on the candidate. Of these, 54.5%, become related it its imagéticas characterizations and 45.5% its candidacy. How much to the construction of the theoretical stage it sends to the workmanships that include the universe of the communication, of the propaganda ideological politics and, mainly, in the Brazilian optics. It is looked, also, to describe the trajectory politics of Affonso Penna, having as deep cloth of the environment politician. As method of collection of data, one cites the bibliographical research and you register and as inquiry instrument the content analysis.(AU)